2020
DOI: 10.1016/j.cej.2020.124465
|View full text |Cite
|
Sign up to set email alerts
|

Novel Fe-Mn binary oxide-biochar as an adsorbent for removing Cd(II) from aqueous solutions

Abstract: In this study, a pristine biochar (BC) and Fe-Mn binary oxide-biochar (FMBC) were prepared using Pennisetum sp. straw as the feedstock for Cd(II) removal from aqueous solutions. Scanning electron microscopy (SEM) coupled with energy dispersive X-ray spectroscopy (EDX), X-ray photoelectron spectroscopy (XPS), X-ray diffraction (XRD), Fourier transform infrared (FTIR) spectroscopy and specific surface area (SSA) analyses revealed the physico-chemical characteristics of the pristine and designer adsorbents, sugge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
49
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 223 publications
(49 citation statements)
references
References 61 publications
(68 reference statements)
0
49
0
Order By: Relevance
“…Furthermore, researchers suggested that iron (Fe) oxides could reduce the mobility of PTEs (especially As) in the soil, and thus mitigate PTE bioavailability and leaching potential (Qiao et al, 2019;Tang et al, 2020;. Studies also suggested the feasibility of using biochar loaded Fe materials to remove As and other toxic elements from aqueous solutions (e.g., Niazi et al, 2018;Xia et al, 2019;Yin et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, researchers suggested that iron (Fe) oxides could reduce the mobility of PTEs (especially As) in the soil, and thus mitigate PTE bioavailability and leaching potential (Qiao et al, 2019;Tang et al, 2020;. Studies also suggested the feasibility of using biochar loaded Fe materials to remove As and other toxic elements from aqueous solutions (e.g., Niazi et al, 2018;Xia et al, 2019;Yin et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…The structure and properties of the materials were further analyzed by nitrogen adsorption desorption experiments. According to the classification of IUPAC, its isotherm is typical type IV 15 . In addition, the desorption hysteresis suggested that PBC was a kind of mesoporous material with lamellar structure and nZVI/PBC was a material with both micropores and mesopores (Figure 1(g)).…”
Section: Resultsmentioning
confidence: 97%
“…The O1s spectrum had three peaks ( Figure 3 d): the peak of 531.6 eV can be ascribed to the lattice oxygen (CO, C=O) [ 28 ]; the peaks of 532.6 eV and 530.5 eV are attributed to the oxygen from organic matter (–OH or C–O–C) [ 29 ] and inorganic matter (MO and M–OH, M was metal), respectively [ 28 ]. The spectrum of Al2p and Mn2p3/2 represented elemental aluminum and manganese from Al 2 O 3 and MnO ( Figure 3 e,f), respectively [ 30 ]. The loaded Al/Mn oxides with different chemical states on the surface of AMKBC 3/4 could react with Cr 2 O 7 2− and HCrO 4 − through a complex reaction and electrostatic attraction, which enhanced Cr(VI) removal (Equations (8) and (9)).…”
Section: Resultsmentioning
confidence: 99%